Bacterial resistance in the treatment of pneumonia in hospital patients: a systematic review (Research, Society and Development, 2022)
Objective: identify the main bacteria resistant to broad drugs associated with the development of pneumonia in hospital patients from 2017 to 2022 worldwide, comparing the agents identified before and during the pandemic due to COVID-19. Methodology: The articles were searched in the Scielo, PubMed and UpToDate databases following the guidelines of the Preferred ReportingItems for Systematic Reviews and Meta-Analyses (PRISMA). The ‘’PVOS’’ strategy (population, variables, outcomes and study) was used to select the articles analyzed in the review. The descriptors standardized by the ‘’Descritores em Ciências da Saúde’’ were used: pneumonia, antibacterials, bacterial drug resistance, bacterial multiple drug resistance for bibliographic survey. Included in this systematic review, analytical observational studies, articles of published research, case studies, systematic reviews and epidemiological, microbiological, and molecular surveillance studies. Results: After the screening process, removal of duplicate articles and analysis of inclusion criteria, 27 articles were identified as eligible for this systematic review. Conclusion: The results of this systematic review provide evidence of the main bacteria causing pneumonia in hospitalized patients worldwide, as well as the resistance profile in the case of multidrug-resistant organisms, in addition to identifying treatment alternatives for these agents.